Metaphysical dualism in "Enneads" by Plotinus - Woszczyk, Agnieszka (Folia Philosophica, 2006)
The main problem of "Enneads" by Plotinus comes down to showing the possibility of the constitution of multiplicity on the assumption of emanative monism. Ontic unity-multiplicity requires an explanation of both the source of multiplicity and unity, which questions the legitimacy of traditional interpretations in the categories of principial monism. The article is an attempt to re-interpret the philosophy by Plotinus from the perspective of its connections with Plato's agrapha dogmata, i.e. the categories of principle dualism.